Nutrient fluxes in the Changjiang River estuary and adjacent waters - a modified box model approach - 王晓红 俞志明 樊伟 宋秀贤 曹西华 袁涌铨 (Chinese journal of oceanology and limnology, 2015)
To solve nutrient flux and budget among waters with distinct salinity difference for water-salt-nutrient budget, a traditional method is to build a stoichiometrically linked steady state model. However, the traditional way cannot cope appropriately with those without distinct salinity difference that parallel to coastline or in a complex current system, as the results would be highly affected by box division in time and space, such as the Changjiang (Yangtze) River estuary (CRE) and adjacent waters (30.75°2–31.75°N, 122°10′–123°20′E). Therefore, we developed a hydrodynamic box model based on the traditional way and the regional oceanic modeling system model (ROMS). Using data from four cruises in 2005, horizontal, vertical and boundary nutrient fluxes were calculated in the hydrodynamic box model, in which flux fields and the major controlling factors were studied. Results show that the nutrient flux varied greatly in season and space. Water flux outweighs the nutrient concentration in horizontal flux, and upwelling flux outweighs upward diffusion flux in vertical direction (upwelling flux and upward diffusion flux regions overlap largely all the year). Vertical flux in spring and summer are much greater than that in autumn and winter. The maximum vertical flux for DIP (dissolved inorganic phosphate) occurs in summer. Additional to the fluxes of the Changjiang River discharge, coastal currents, the Taiwan Warm Current, and the upwelling, nutrient flux inflow from the southern Yellow Sea and outflow southward are found crucial to nutrient budgets of the study area. Horizontal nutrient flux is controlled by physical dilution and confined to coastal waters with a little into the open seas. The study area acts as a conveyer transferring nutrients from the Yellow Sea to the East China Sea in the whole year. In addition, vertical nutrient flux in spring and summer is a main source of DIP. Therefore, the hydrodynamic ROMS-based box model is superior to the traditional one in estimating nutrient fluxes in a complicated hydrodynamic current system and provides a modified box model approach to material flux research.